Maternal near miss – towards a standard tool for monitoring quality of maternal health care - Say, Lale; Souza, João Paulo; Pattinson, Robert C. (Best practice & research. Clinical obstetrics & gynaecology, 2009)
Maternal mortality is still among the worst performing health indicators in resource-poor settings. For deaths occurring in health facilities, it is crucial to understand the processes of obstetric care in order to address any identified weakness or failure within the system and take corrective action. However, although a significant public health problem, maternal deaths are rare in absolute numbers especially within an individual facility. Studying cases of women who nearly died but survived a complication during pregnancy, childbirth or postpartum (maternal near miss or severe acute maternal morbidity) are increasingly recognized as useful means to examine quality of obstetric care. Nevertheless, routine implementation and wider application of this concept in reviewing clinical care has been limited due to the lack of a standard definition and uniform case-identification criteria. WHO has initiated a process in agreeing on a definition and developing a uniform set of identification criteria for maternal near miss cases aiming to facilitate the reviews of these cases for monitoring and improving quality of obstetric care. A list of identification criteria was proposed together with one single definition. This article presents the proposed definition and the identification criteria of maternal near miss cases. It also suggests procedures to make maternal near miss audits operational in monitoring/evaluating quality of obstetric care. The practical implementation of maternal near miss concept should provide an important contribution to improving quality of obstetric care to reduce maternal deaths and improve maternal health.